La difficile construction d’une expertise européenne indépendante - Jean-Pierre Galland (Revue d'anthropologie des connaissances)
This article describes the notified bodies’ invention, by the European Commission, in the follow-on of the New Approach to Technical Harmonisation and Standards framework. These bodies, whose function is to certify that products entering the European Market conform to essential safety requirements worded inside diverse directives, are appointed by Member States but compete against one another at the European level. The article considers the consequences of this situation and the Commission efforts so to maintain both the independence and the competences of these new European experts. Based on an empirical work, it proposes two ways for complementary research: on one hand, after a first analysis of the certification methods used in the medical devices sector, it suggests to investigate more deeply the “black box” of this new and barely visible expertise; on the other hand, it invites to systematic studies on the population of notified bodies, whose diffuse and discreet acts take part significantly in markets and risks regulation in Europe.